Austerity Redux: The Post‐pandemic Wave of Budget Cuts and the Future of Global Public Health. Issue 1 (23rd November 2021) - Kentikelenis, Alexander; Stubbs, Thomas
Abstract: The convergence of health, economic and social crises over the past 1.5 years has posed profound questions over the direction of travel for the world after COVID‐19. The narrative emerging out of major international organizations like the International Monetary Fund stresses avoiding a 'divergent recovery', whereby some countries steam ahead with high growth rates underpinned by robust government interventions and others fall further behind. In this account, crisis aftermath should not witness budget cuts, but investment in employment and human capital formation. So, is austerity a thing of the past? In this article, we review available evidence, focusing on public spending projections by the IMF and the precise content of IMF lending arrangements. Overall, we find that abandonment of the austerity argument is partially true right now, and questionable in the medium‐term. Our analysis of public expenditure projections reveals that by 2023, 83 out of 189 countries will face contractions in government spending compared to their 2010s average, thereby exposing a cumulative total of 2.3 billion people to the socio‐economic consequences of budget cuts. Most of the contracting countries will be middle‐income, while public spending in low‐income countries is expected to stagnate at low levels. Further, the IMF's lending arrangements reveal the return of extensive austerity measures and structural reforms, reminiscent of the organization's past policy advice. Drawing on these findings, we elaborate on how this will likely impact global public health. Abstract : The convergence of health, economic and social crises over the past 1.5 years has posed profound questions over the direction of travel for the world after COVID‐19. The narrative emerging out of major international organizations like the International Monetary Fund stresses avoiding a 'divergent recovery', whereby some countries steam ahead with high growth rates underpinned by robust government interventions and others fall further behind. In this account, crisis aftermath should not witness budget cuts, but investment in employment and human capital formation. So, is austerity a thing of the past? In this article, we review available evidence, focusing on public spending projections by the IMF and the precise content of IMF lending arrangements. Overall, we find that abandonment of the austerity argument is partially true right now, and questionable in the medium‐term. Our analysis of public expenditure projections reveals that by 2023, 83 out of 189 countries will face contractions in government spending compared to their 2010s average, thereby exposing a cumulative total of 2.3 billion people to the socio‐economic consequences of budget cuts. Most of the contracting countries will be middle‐income, while public spending in low‐income countries is expected to stagnate at low levels. Further, the IMF's lending arrangements reveal the return of extensive austerity measures and structural reforms, reminiscent of the organization's past policy advice. Drawing on these findings, we elaborate on how this will likely impact global public health.